The pre-basaltic sediments and the Lower Basalts at Kangerdlugssuaq, East Greenland: their stratigraphy, lithology, palaeomagnetism and petrology - Nielsen, Troels F. D.; Soper, N. J.; Brooks, C. Kent; Faller, Angela M.; Higgins, Alan C.; Matthews, David W. (Meddelelser om Grønland. Geoscience, 1981)
This paper presents a new 1:40 000 topographic and geological map of the area around Miki Fjord and l. C. Jacobsen Fjord, East Greenland. The post-Precambrian sedimentary succession, the Kangerdlugssuaq Group, begins with the Ryberg Formation (Campanian to Danian (?)) and continues into the Vandfaldsdalen Formation of Late Paleocene age. These sediments were laid down in a basin which subsequently became filled and covered by basaltic rocks of the Blosseville Group, including lavas, hyaloclastites, tuffs and breccias. Considerable facies variations are apparent in both the sediments and volcanics indicating that the basin deepened in an easterly direction. Palaeomagnetic measurements confirm previous results for the Blosseville Group on the Lower Basalts but do not yet entirely eliminate the possibility that some of the succession has normal polarity. Petrographically the volcanics include picrites (oceanites and ankaramites), olivine tholeiites, tholeiites and tholeiitic andesites. They have almost all suffered alteration up to greenschist facies and some show evidence of sedimentary contamination. They are all of tholeiitic affinity and are Fe and Ti enriched when compared to normal ocean ridge basalts. They are however much more variable in composition than the overlying Plateau Basalts and have not been produced in such large volumes. It is suggested that a primary picritic magma gave rise to the oceanites and ankaramites by olivine and clinopyroxene fractionation and accumulation. The olivine tholeiites, which appear to be separated from the picrites by a compositional gap, may be derived from a different parental magma. Petrological parallels are drawn with other provinces.